A theology of pastoral multiplicity. Issue 3 (22nd June 2020) - Gano Lindner, Cynthia
Abstract: The contemporary moment is characterized by liquidity and difference. "Liquidity" means rapidly changing social structures, accelerations in consumption, and constantly changing personal and group identities. In this increasingly diverse context, encounters with difference are not only inevitable, they are essential—and can be transformative for our understandings of our multiple selves, for our pastoral encounters with others, and for our theological imagination, as well. Viewing the self, especially the pastor's self, as a collection of multiple selves, identities, and performances illumines pastoral leadership; pastors who claim their multiplicity more wholly meet "others" when encountering difference. The triune God reveals divine multiplicity, so pastors who claim their multiplicity as their identity thereby make a theological claim.